Annual Statistical Abstract for Tamil Nadu 1979-80 - Planning Commission (Planning Commission, 1979)
The Total of the area Figures of the taluks will not tally with the district figures the taluk-area figures represent the land use' areas lack and derived from the figures supplied by the Tamil Nadu Directorate of Survey and Land records, While those of the district represent "Geographical Area" Supplied by the Surveyor to General of India.
Department of Statistics Madras